"Saving lives with nirmatrelvir/ritonavir one transplant patient at a time". Issue 2 (27th February 2023) - Belden, Katherine A.; Yeager, Sarah; Schulte, Jamie; Cantarin, Maria P. Martinez; Moss, Sean; Royer, Tricia; Coppock, Dagan
Abstract: Background: Solid organ transplant (SOT) recipients are at risk of complications from COVID‐19. Nirmatrelvir/ritonavir (Paxlovid) can reduce mortality from COVID‐19 but is contraindicated in patients receiving calcineurin inhibitors (CI), which depend on cytochrome p4503A (CY3PA). In this study, we aim to show the feasibility of nirmatrelvir/ritonavir administration to SOT recipients receiving CI with coordination of medication management and limited tacrolimus trough monitoring. Methods: We reviewed adult SOT recipients treated with nirmatrelvir/ritonavir from 4/14 to 11/1/2022 and assessed for changes in tacrolimus trough and serum creatinine after therapy. Results: Of 47 patients identified, 28 were receiving tacrolimus and had follow‐up laboratory testing. Patients had a mean age of 55 years, 17 (61%) received a kidney transplant and 23 (82%) received three or more doses of SARS‐CoV‐2 mRNA vaccine. Patients had mild‐moderate COVID‐19 and started nirmatrelvir/ritonavir within 5 days of symptom onset. Median baseline tacrolimus trough concentration was 5.6 ng/mL (Interquartile range 5.1–6.7), while median follow‐up tacrolimus trough concentration was 7.8 ng/mL (Interquartile range 5.7–11.5, p = 0.0017). Median baseline and follow‐up serum creatinine levels were 1.21 mg/dL (Interquartile range 1.02–1.39) and 1.21 mg/dL (interquartile range 1.02–1.44, p = 0.3162), respectively. One kidney recipient had a follow up creatinine level >1.5 times baseline. No patients were hospitalized or died from COVID‐19 in the follow up period. Conclusion: While administration of nirmatrelvir/ritonavir resulted in a significant increase in tacrolimus concentration, this did not result in significant nephrotoxicity. Early oral antiviral treatment in SOT recipients is feasible with medication management, even with limited tacrolimus trough monitoring. Abstract : While administration of nirmatrelvir/ritonavir to 28 solid organ transplant (SOT) recipients resulted in a significant increase in tacrolimus concentration, this did not result in significant nephrotoxicity. Early oral antiviral therapy for COVID‐19 in SOT recipients is feasible with appropriate medication management, even when tacrolimus trough monitoring is limited.